Health performance and economic growth in sub-Saharan Africa: new evidence based on quantile regressions - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2023)
The present study investigates the nexus between health performance dynamics and economic growth in 43 countries in sub-Saharan Africa for the period 2004-2018. Four health performance dynamics are used, notably: total life expectancy, male life expectancy, female life expectancy and risk of maternal death. The empirical evidence is based on quantile regressions in order to put into perspective the conditional distribution of economic growth. The following findings are established: (i) total life expectancy and male life expectancy increase economic growth exclusively in the 10th and 90th quantiles of economic growth; (ii) female life expectancy boosts economic growth in the 90th quantile of economic growth and (iii) the risk of maternal death reduces economic growth in the 75th and 90th quantiles of economic growth. Policy implications are discussed. The study complements the literature on the nexus between health performance and economic growth by assessing the nexuses throughout the conditional distribution of economic growth.
Keywords: D31; I10; I32; K40; O55; 330; health performance; economic growth; sub-Saharan Africa; quantile regression